Maternal and neonatal outcome in pregnant women undergone induction of labor at Muhimbili National Hospital, Dar Es Salaam, Tanzania - Shweta Jaiswal; Willbroad Kyejo; Charles Kilewo (BMC, 2024)
Abstract Introduction Labor induction is a common obstetric intervention aimed at initiating labor when spontaneous onset is delayed or deemed necessary for maternal or fetal well-being. Despite its widespread use, the practice's impact on maternal and neonatal outcomes remains a subject of ongoing research and debate. This study aims to evaluate the maternal and neonatal outcomes associated with labor induction in a tertiary hospital setting in Tanzania. Methodology A descriptive analytical cross-sectional study was conducted over a seven-month period from January 2021 to July 2021 at Muhimbili National Hospital in Dar es Salaam, Tanzania. A total of 120 pregnant women who underwent labor induction during this period were included in the analysis. Data on maternal demographics, obstetric characteristics, indications for induction, methods of induction, labor outcomes, and neonatal outcomes were collected from medical records and analyzed descriptively. Results Among 4773 deliveries during the study period, 120 women underwent labor induction, accounting for 120 (2.5%) of all deliveries. The most common indications for induction were postdate pregnancy 60 (50%), hypertensive disorders of pregnancy 38 (31.7%), and premature rupture of membranes 22 (17.5%). The majority of induced women 74 (61.7%) delivered vaginally, with 46 (38.3%) undergoing cesarean section. Maternal complications were minimal, with the most common being failed induction of labor 17 (14.2%). Neonatal outcomes were generally positive, with 120 (100%) of neonates having Apgar scores of 7 or higher at five minutes, although 10 (8.3%) required admission to the neonatal ward for further care. Conclusion Labor induction at Muhimbili National Hospital demonstrated favorable maternal and neonatal outcomes, with low rates of maternal complications and positive neonatal Apgar scores. Postdate pregnancy emerged as the most common indication for induction. While the study highlights the benefits of labor induction, its retrospective nature and single-center setting limit the generalizability of findings. Prospective studies with larger sample sizes are warranted to validate these findings and inform evidence-based obstetric practices.